Distribution of conjunctive and disjunctive forms in Xitsonga - Lee, Seunghun J.; Hlungwani, Crous (Stellenbosch Papers in Linguistics Plus, 2017)
The conjunctive and disjunctive forms in Xitsonga are examined with the purpose of presenting the distribution of these forms. While verbs in the conjunctive form are followed by some elements, the disjunctive is used when no element follows the verb. Xitsonga follows these basic patterns observed in other Bantu languages, but previous theories cannot explain all of the cases in which the conjunctive and disjunctive forms are distinguished. In previous work, three major approaches have been proposed: the constituency approach, the focus-based approach, and the information packaging approach. Xitsonga supports but also provides counterevidence to all of these approaches. This paper also re-examines the claim that the presence of conjunctive/disjunctive distinctions only exists in the present tense. Following Creissels (2014), we report that the conjunctive/disjunctive dichotomy is present in other tenses as well when prosodic patterns such as penultimate lengthening are further examined.